If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4n + -5 = 9 + 2n Reorder the terms: -5 + 4n = 9 + 2n Solving -5 + 4n = 9 + 2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2n' to each side of the equation. -5 + 4n + -2n = 9 + 2n + -2n Combine like terms: 4n + -2n = 2n -5 + 2n = 9 + 2n + -2n Combine like terms: 2n + -2n = 0 -5 + 2n = 9 + 0 -5 + 2n = 9 Add '5' to each side of the equation. -5 + 5 + 2n = 9 + 5 Combine like terms: -5 + 5 = 0 0 + 2n = 9 + 5 2n = 9 + 5 Combine like terms: 9 + 5 = 14 2n = 14 Divide each side by '2'. n = 7 Simplifying n = 7
| 3c-2c=16 | | 63=50+C-40/4 | | y=3(9)-12 | | 2x^3-8x=5 | | 3x(15-x)=150 | | 9(n+4)=8+5n | | Axb+25=25 | | 2m+3n=6 | | 2q-q+3q-q=20 | | 3p+pq+2pr= | | 6h+8=12 | | .4+98234= | | 2x^3-8x-5=0 | | 4[2t-(3-t)+5]=4(1-x) | | 16=k/3-111 | | 6x+2x+4=3x+3-5x-9 | | 11t+2t-12t=18 | | 9h+5=16 | | 6-2(x+7)=-4x-12 | | 71.77=c+36.82 | | (x-y)*y(dx)=x^2(dy) | | 2-20f=-19f-10 | | =(5x^5+4x^4+6)-(-12x^4+8x^5-18) | | 5a-4a=14 | | 18h=20+19h | | (2x^3-5x^2+7x)(-x^2y)= | | w-6.38=4.85 | | 10b+7+18=7+9b | | q+30=6q | | 3(2t-4)=-4(x+1) | | 5-3(x-3)=2(2-x)-8 | | -10p+8=-6-8p-4p |